THE EFFECT OF PRICE, LOCATION, AND SERVICE QUALITY ON CUSTOMER SATISFACTION (CASE STUDY: A CAR WORKSHOP IN KAYUPUTIH VILLAGE, PANJI DISTRICT, SITUBONDO REGENCY) - Susi Radila; Lusi Endang Sri D; Lisma Dian Kartika Sari (Yayasan Amanah Nur Aman, 2025)
This study uses a quantitative approach. Quantitative research is a type of research that is systematic, planned, and clearly structured, from formulation to research design. Based on the results of the SPSS calculations above, it can be concluded that the correlation coefficient of 0.851 indicates the influence of price, location, and service quality on customer satisfaction. In this case, the number of respondents was 100. The R table value was obtained by calculating the degree of freedom (df) = 100 – 2 = 98, with df = 98 and alpha = 0.05, resulting in an R-table value of 0.198. Therefore, r calculated > r table, 0.851 > 0.198, meaning the null hypothesis is rejected and the alternative hypothesis Ha is accepted, indicating that there is an influence of price, location, and service quality on customer satisfaction, which is a high correlation. The calculated t-value for price is 8.096 and the t-table value is 1.985, meaning that the comparison between the t-table value and the calculated t-value (8.096 < 1.985) shows that the t-table value is greater than the calculated t-value. Therefore, it can be concluded that there is an influence of the price variable on customer satisfaction simultaneously, so Ha is accepted. The calculated t-value for location is 2.426 and the table value is 1.985, meaning that the table value is greater than the calculated value (2.426 < 1.985). Therefore, it can be concluded that there is a simultaneous influence of the location variable on customer satisfaction, so Ha is accepted and Ho is rejected. The calculated t-value for service quality is 5.501 and the table value is 1.985, meaning that the table value is greater than the calculated value (5.501 < 1.980). Therefore, it can be concluded that there is a simultaneous influence of the service quality variable on consumer satisfaction, so Ha is accepted and Ho is rejected.